1974
DOI: 10.1002/neu.480050204
|View full text |Cite
|
Sign up to set email alerts
|

The protein subunit of calf brain neurofilament

Abstract: A preparation of the protein subunits from calf neurofilaments has been obtained. Axon segments from an homogenate of calf brain white matter have been concentrated by a subcellular fractionation procedure. After further steps to achieve a complete elimination of unbound lipid, the neurofilament protein was dissolved in 4M guanidine hydrochloride solutions. The neurofilalment subunit was the major constituent of the guanidine hydrochloride extracts; other proteins of higher molecular weight were eliminated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 25 publications
4
55
0
Order By: Relevance
“…This protein migrates with one of the major polypeptides of rat brain myelin, but electron micrographs and gels of the vesicle preparation contain no indication of a myelin contamination. This protein also corresponds closely in molecular weight to the subunit protein of neurofilaments (26). It has been suggested (27) that synaptic vesicles have bound neurofilaments subunits.…”
Section: Distribution and Biochemical Purity Of Synaptosomalmentioning
confidence: 56%
“…This protein migrates with one of the major polypeptides of rat brain myelin, but electron micrographs and gels of the vesicle preparation contain no indication of a myelin contamination. This protein also corresponds closely in molecular weight to the subunit protein of neurofilaments (26). It has been suggested (27) that synaptic vesicles have bound neurofilaments subunits.…”
Section: Distribution and Biochemical Purity Of Synaptosomalmentioning
confidence: 56%
“…Both smooth muscle and nervous tissue contain heterogeneous cell populations which impose the time-consuming steps of fractionation to obtain homogeneous cell types as in brain (1,16,21,25), or to obtain complex organelles such as the dense bodies of gizzards (17,18,26,28) prior to application of procedures to enrich 10-nm filaments. All techniques used on mammalian cells to date require anywhere from a few to 15 days to attain significant enrichment (1, 16-18, 21, 26, 28) of morphologically distinguishable filaments.…”
mentioning
confidence: 99%
“…In neuroblastoma cells the bundles of 100 A filaments are located in the perinuclear region and extend out into the cell processes, where they are oriented parallel to the long axis of the process (9, 10). Neurofilaments approximately 100 A in diameter have been isolated and partially characterized from the giant axon of squid (11) and from axons of calf brain (12)(13)(14).Very little is known about the function of these filaments, though it has been suggested that they play a role in axoplasmic transport (15, 16). The major reason for this lack of understanding is that no procedure has been discovered that specifically interferes with the integrity of these filaments.…”
mentioning
confidence: 99%